Targeting the Heme Oxygenase 1/Carbon Monoxide Pathway to Resolve Lung Hyper-Inflammation and Restore a Regulated Immune Response in Cystic Fibrosis - Di Pietro, Caterina; Öz, Hasan H.; Murray, Thomas S.; Bruscia, Emanuela M. (Frontiers in Pharmacology, 2020)
In individuals with cystic fibrosis (CF), lung hyper-inflammation starts early in life and is perpetuated by mucus obstruction and persistent bacterial infections. The continuous tissue damage and scarring caused by non-resolving inflammation leads to bronchiectasis and, ultimately, respiratory failure. Macrophages (MΦs) are key regulators of immune response and host defense. We and others have shown that, in CF, MΦs are hyper-inflammatory and exhibit reduced bactericidal activity. Thus, MΦs contribute to the inability of CF lung tissues to control the inflammatory response or restore tissue homeostasis. The non-resolving hyper-inflammation in CF lungs is attributed to an impairment of several signaling pathways associated with resolution of the inflammatory response, including the heme oxygenase-1/carbon monoxide (HO-1/CO) pathway. HO-1 is an enzyme that degrades heme groups, leading to the production of potent antioxidant, anti-inflammatory, and bactericidal mediators, such as biliverdin, bilirubin, and CO. This pathway is fundamental to re-establishing cellular homeostasis in response to various insults, such as oxidative stress and infection. Monocytes/MΦs rely on abundant induction of the HO-1/CO pathway for a controlled immune response and for potent bactericidal activity. Here, we discuss studies showing that blunted HO-1 activation in CF-affected cells contributes to hyper-inflammation and defective host defense against bacteria. We dissect potential cellular mechanisms that may lead to decreased HO-1 induction in CF cells. We review literature suggesting that induction of HO-1 may be beneficial for the treatment of CF lung disease. Finally, we discuss recent studies highlighting how endogenous HO-1 can be induced by administration of controlled doses of CO to reduce lung hyper-inflammation, oxidative stress, bacterial infection, and dysfunctional ion transport, which are all hallmarks of CF lung disease.